The social construction of nurse educator professional identities: Exploring the impact of a community of practice through participatory action research. (5th April 2022) - Woods, Andrew; Cashin, Andrew; Horstmanshof, Louise
Abstract: Aims: The aim of the study was to explore whether, and how, professional nurse educator identity is co‐constructed by a community of practice. Design: A critical participatory action research (PAR) methodology was used as it extends the principles of action research by seeking purposeful and sustainable social change that recognizes participants as researchers and generators of knowledge. Methods: Twenty‐two sector‐based nurse educators employed as either nurse educators or clinical nurse educators participated in the critical PAR. Multiple methods of data generation were pursued in a cyclic and sequential manner consistent in an action research process. Three distinct phases of the research across 2015–2017 involved the generation of data before, during and after the establishment of a nurse educator community of practice. A social constructionist lens of analysis was used to explore the social and relational outcomes. The COREQ checklist was used to appraise the study report. Results: A sustained period of community of practice engagement enhanced the participants' relationships and shifted their perceived professional identities towards being validated nurse educators with a stronger collective sense of their roles. Conclusion: For this group of nurse educators, participation in the research resulted in collective meaning‐making, praxis, knowledge generation and the co‐construction of their professional identities. Implications: Nurses struggle to authenticate sector‐based nurse educator professional identities. It was found that a purposeful community of practice facilitates the co‐construction of nurse educator professional identities. Currently, under‐used in nurse educator research, PAR and community of practice theory are recommended for nurses or other health professionals seeking practice development, role validation, retention and satisfaction.